A Nano-Silver Loaded PVA/Keratin Hydrogel With Strong Mechanical Properties Provides Excellent Antibacterial Effect for Delayed Sternal Closure - Pan, Yanjun; Li, Pengfei; Liang, Fubang; Zhang, Jingyi; Yuan, Jiang; Yin, Meng (Frontiers in Bioengineering and Biotechnology, 2021)
Delayed chest closure (DSC) is widely performed during the treatment of congenital heart diseases. However, the high prevalence of surgical site infection (SSI) in patients undergoing DSC affects prognosis negatively. Herein, we designed a suturable poly(vinyl alcohol)/keratin film loaded with silver nanoparticles (AgNPs) as an alternative material for DSC, which was named PVA/Keratin/AgNPs. The PVA/Keratin/AgNPs films exhibited significantly enhanced mechanical strength after crosslinking by sodium trimetaphosphate (STMP). These films were non-toxic, and cells proliferated with good morphology after one week of culture. In addition, PVA/Keratin/AgNPs films provided superior antibacterial ability, as evidenced by the eradication and lower growth rate of Staphylococcus aureus and Escherichia coli. Finally, the PVA/Keratin/AgNPs films were demonstrated to successfully cover the chest cavity temporarily and protect the chest cavity from bacterial infection. These results indicated that the PVA/Keratin/AgNPs films have great prospects to be further exploited for clinical applications in DSC.